Integrated rural development as a means for development benefit to Asia small farmers - Chang, H.T.; International Conference on Rural Development Technology : an Integrated Approach (June 1977 Asian Institute of Technology, Bangkok, Thailand). (1977)
The Asian small farmers must be reached directly if they are to share in the benefits of development. In order to reach them, channels must be built for delivery of goods, technology, services and credit. Farmer organizations are essential links in this delivery system and, thus, are crucial to rural development. In the long run, rural development must embrace all activities for the betterment of rural livelihood, However, to lump many activities of a different nature together and call the product "integrated" has led to the failure of many projects. True integration should be built around activities directed at solving critical farm level problems faced by large numbers of farmers.
Abstract -- A. To define rural development -- B. Rural development and capital/technology intensive projects -- C. Asian rural structure constraint rural development -- D. Need of reemphasizing farmers organizations -- E. The question of integration.
Typescript.
Paper presented at the International Conference on Rural Development Technology : an Integrated Approach, Asian Institute of Technology, Bangkok, Thailand, June 1977.
Keywords: Rural development -- Small farmers -- Asia